Integration of Islamic values in mathematical modeling through Model Eliciting Activities Based Learning - Asfira Zakiatun Nisa'; Imam Rofiki; Abdussakir Abdussakir (Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Mathematics learning integrated with Islamic values needs to be carried out to provide opportunities for students to study various sciences in one scope. Many Islamic schools (madrasah) still need to be taught by integrating mathematics and Islam. This study aims to introduce Islamic integrated mathematical modelling through Model Eliciting Activities based learning. The research method used was qualitative, with a literature review. This research used the Model Eliciting Activities, which guides learning integrated Islamic mathematics. Thus, educaters can apply the learning steps in class and can develop this research more broadly.